Seth Tobocman, Disaster and Resistance: Comics and Landscape for the Twenty First Century (Altre Modernità, 2011)
Seth Tobocman, Disaster and Resistance: Comics and Landscape for the Twenty First Century (Oakland, AK Press, 2008, 170 pp. ISBN 9781904859765) di Cinzia Scarpino